A Gene Network Perspective on Axonal Regeneration - Van Kesteren, Ronald E.; Mason, Matthew R.; MacGillavry, Harold D.; Smit, August B.; Verhaagen, Joost (Frontiers in Molecular Neuroscience, 2011)
The regenerative capacity of injured neurons in the central nervous system is limited due to the absence of a robust neuron-intrinsic injury-induced gene response that supports axon regeneration. In peripheral neurons axotomy induces a large cohort of regeneration-associated genes (RAGs). The forced expression of some of these RAGs in injured neurons has some beneficial effect on axon regeneration, but the reported effects are rather small. Transcription factors (TFs) provide a promising class of regeneration-associated genes. TFs are hubs in the regeneration-associated gene network, and potentially control the coordinate expression of many regeneration-associated genes simultaneously. Here we discuss the use of combined experimental and computational methods to identify novel regeneration-associated TFs with a key role in initiating and maintaining the RAG-response in injured neurons. We propose that a relatively small number of hub TFs with multiple functional connections in the RAG-network might provide attractive new targets for gene-based and/or pharmacological approaches to promote axon regeneration in the central nervous system.